Exploring linguistic predictors of academic reading comprehension among ESL undergraduates at a public university: a preliminary study - Yap, Ngee Thai; Chan, Mei Yuit; Paiman, Norazha (UPSI Press, 2024)
For many years, ESL educators have placed significant emphasis on improving the reading abilities of primary and secondary education students. Nonetheless, despite these efforts, many university students still encounter difficulties in comprehending academic reading materials. This inadequacy in reading comprehension may be ascribed, at least in part, to the insufficient development of metalinguistic competence, which includes a set of linguistic skills, such as morphology, syntax, and vocabulary. Previous empirical studies have provided compelling evidence of the role of morphological awareness, syntactic awareness, and lexical knowledge in reading comprehension across various age groupssuch as children and adolescents. Notwithstanding these findings, the precise role and contributionsof each determinant remains inconclusive and contradictory, particularly for university students. Hence, this pilot study aimed to validate the adapted instruments used and to bridge the existing scientificlacunae on the linguistic determinants that could predict reading comprehension among Malaysian ESL undergraduates. This study draws upon three prominent theoretical underpinnings: the Reading Systems Framework, the Vocabulary Knowledge-Reading Comprehension Model, and the Automaticity Reading Theory. This study adopteda quantitative approach with a correlational design and recruited ESL undergraduates (n=35) from a public university. Five tests were administered, which included Morphological Awareness Test, Syntactic Awareness Test, Vocabulary Levels Test,Word Associates Test, and Reading Comprehension Test. Data were analysed using statistical techniques, such as descriptive statistics, normality testing, reliability, and Pearson product-moment correlation analysis. The findings revealed significant correlations between all linguistic determinants and reading comprehension, establishing promising groundwork for further large-scale study. This preliminary work not only contributes to the validation of measurement instruments in the Malaysian ESL context but also offers valuable insights into the metalinguistic dimensions of academic reading at the tertiary level so as to address a crucial scientific lacunae in the literature on L2 reading comprehension.